Wide-Field High-Speed Scanning Acoustic/Photoacoustic Microscopy for Whole-Body Imaging of Small Animals - Joongho Ahn; Hyoseok Choi; Seongjun Lim; Jin Young Kim; Jeongwoo Park (Biosensors)
Photoacoustic (PA) imaging combines optical contrast with ultrasound (US) detection, enabling high-resolution imaging of biological tissues with greater penetration depth than conventional optical techniques. Among its various implementations, photoacoustic microscopy (PAM) achieves micrometer-scale resolution by focusing laser excitation and detecting ultrasonic signals, allowing for the detailed visualization of microvascular structures and fine tissue morphology. Over the last decade, PAM imaging speed has significantly increased by adopting PA scanners that steer optical and acoustic waves. However, these scanners must be placed after focusing optics to co-align the waves on a spot, which creates bent focal lines along the scanning direction and limits the scanning range. To achieve wide-field imaging, various image mosaic algorithms have been applied, but these methods require multiple manual operations, which take more time than the imaging itself. In this study, we developed a wide-field, high-speed scanning acoustic/photoacoustic microscopy (SA/PAM) system equipped with a transparent ultrasound transducer and a moving magnet linear stage, which eliminates the need for complex mosaic algorithms. This system enables wide-field imaging up to 50 × 50 mm2 while maintaining high lateral resolution, achieving an imaging speed of 50 Hz in a B-scan image. Through in vivo mouse US/PA imaging, the system demonstrated its capability to visualize blood vessels and organs across the whole body of small animals. These findings suggest that the SA/PAM system is a practical tool for biomedical research, allowing for efficient visualization of vascular networks and anatomical structures in various preclinical studies.